Theanine attenuates memory impairments induced by klotho gene depletion in mice. Issue 1 (21st December 2018) - Nguyen, Bao Trong; Sharma, Naveen; Shin, Eun-Joo; Jeong, Ji Hoon; Lee, Sung Hoon; Jang, Choon-Gon; Nah, Seung-Yeol; Nabeshima, Toshitaka; Yoneda, Yukio; Kim, Hyoung-Chun
Abstract : Theanine (γ-glutamylethylamide), an amino acid in tea, is a putative neuroprotective and antioxidant compound capable of improving lifespan and cognitive function. Abstract : Theanine (γ-glutamylethylamide), an amino acid in tea, is a putative neuroprotective and antioxidant compound capable of improving lifespan and cognitive function. Because we previously reported cognitive dysfunction in klotho mutant mice via down-regulation of janus kinase 2 (JAK2) and signal transducer and activator of transcription3 (STAT3), M1 muscarinic cholinergic receptor (M1 mAChR), and ERK signaling, we, therefore, investigated whether self-administration of theanine affects memory dysfunction in response to klotho gene depletion in mice, and whether theanine modulates the JAK2/STAT3, M1 mAChR, and ERK signaling network. Theanine significantly attenuated memory impairments in klotho mutant mice. Moreover, theanine self-administration significantly attenuated inhibitions of JAK2/STAT3 phosphorylation, M1 mAChR expression, and ERK1/2 phosphorylation in the hippocampus of klotho mutant mice. Consistently, AG490, a JAK2/STAT3 inhibitor, dicyclomine, an M1 mAChR antagonist, or U0126, an ERK1/2 inhibitor, significantly counteracted theanine-induced attenuation of memory impairment induced by klotho gene depletion in mice. Our study suggests that theanine attenuates memory impairments in a genetic aging model via up-regulation of JAK2/STAT3, M1 mAChR, and ERK signaling.